Sustainable Marketing Strategy: Building Brand Loyalty through Eco-Friendly Marketing - Irsandi, Irsandi (Cita konsultindo, 2024)
This study aims to explore the influence of sustainable marketing strategies on brand loyalty through the formation of an environmentally friendly brand image. With increasing consumer awareness of environmental issues, sustainable marketing has become an important element in branding strategies to create long-term relationships with consumers. This study uses a quantitative approach with a survey method, involving 300 environmentally conscious respondents, and analyzing data using the Structural Equation Modeling (SEM) technique. The results showed that green marketing has a significant effect on green brand image, which in turn mediates the relationship between sustainable marketing and brand loyalty. Consumers who perceive a brand as an environmental advocate tend to have higher loyalty to the brand. This finding highlights the importance of transparency and honesty in sustainable marketing to build a positive image and increase consumer loyalty. This study provides important implications for brand managers in developing effective sustainable marketing strategies, as well as for academics in enriching the literature on marketing and brand loyalty. Recommendations for further research include exploring the role of culture and individual values in influencing the relationship between sustainable marketing and brand loyalty.